2011
DOI: 10.1111/j.1365-3040.2011.02406.x
|View full text |Cite
|
Sign up to set email alerts
|

Never too many? How legumes control nodule numbers

Abstract: Restricted availability of nitrogen compounds in soils is often a major limiting factor for plant growth and productivity. Legumes circumvent this problem by establishing a symbiosis with soil-borne bacteria, called rhizobia that fix nitrogen for the plant. Nitrogen fixation and nutrient exchange take place in specialized root organs, the nodules, which are formed by a coordinated and controlled process that combines bacterial infection and organ formation. Because nodule formation and nitrogen fixation are en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
83
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(91 citation statements)
references
References 179 publications
(455 reference statements)
5
83
0
3
Order By: Relevance
“…Symbiotically produced IAA alone or along with other plant hormones involved in several stages of establishment of symbiotic relationship and also transported to the plant for its use. Rhizobial induced local accumulation of auxins stimulates the formation of nodule primordia [32] and also necessary for growth and maintenance of root nodules. Ghosh et al [33] suggested that IAA content produced by the bacterioids in the nodule and supplied to the host plant is the second line of symbiosis apart from nitrogen fixation.…”
Section: Plant Growth Promoting Charactersmentioning
confidence: 99%
“…Symbiotically produced IAA alone or along with other plant hormones involved in several stages of establishment of symbiotic relationship and also transported to the plant for its use. Rhizobial induced local accumulation of auxins stimulates the formation of nodule primordia [32] and also necessary for growth and maintenance of root nodules. Ghosh et al [33] suggested that IAA content produced by the bacterioids in the nodule and supplied to the host plant is the second line of symbiosis apart from nitrogen fixation.…”
Section: Plant Growth Promoting Charactersmentioning
confidence: 99%
“…First, an internal regulation leads to an "auto-regulation of nodule number" (AON) by the host plant, through a systemic feedback repression of nodulation by pre-existing nodules (Reid et al 2011;Mortier et al 2012 for reviews). Deregulated mutants with a hypernodulating phenotype were isolated in several legume species (Novak 2010;Reid et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Most previous experiments on ozone effects on clover were conducted in 61 brassinosteroids and jasmonic acid (JA) suggested as likely candidates for the SDI 85 signal (Mortier et al 2012). Nodulation is also determined by local hormonal 86 regulation, with JA, abscisic acid (ABA) and ethylene together acting as local negative 87 regulators of nodule initiation (Mortier et al 2012). 88…”
Section: Introduction 29mentioning
confidence: 99%